2012
DOI: 10.1002/cbf.2935
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of sesaminol from Sesamum indicum Linn. against oxidative damage in PC12 cells

Abstract: Sesaminol is one component of sesame oil and has been widely used as the stabilizer to extend the storage period of food oil in China. In this study, we tried to investigate the antioxidant activity of sesaminol on rat pheochromocytoma (PC12) cells oxidative damaged by H2 O2 . Cell viability, LDH level and apoptosis of the PC12 cells were assayed after treatment with sesaminol for 3 h and exposure to H2 O2 . Furthermore, superoxide (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and intracellular ROS we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Sesaminol from sesame oil has been reported as an antioxidative compound 37, 38, 39 ; however, little is known about its anticancer effect. To investigate the effect of sesaminol on cancer cells, we exposed human breast cancer MCF7 cells in the presence of various concentrations of sesaminol for 72 h. As shown in Figure 1a, sesaminol dose-dependently inhibited cell growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesaminol from sesame oil has been reported as an antioxidative compound 37, 38, 39 ; however, little is known about its anticancer effect. To investigate the effect of sesaminol on cancer cells, we exposed human breast cancer MCF7 cells in the presence of various concentrations of sesaminol for 72 h. As shown in Figure 1a, sesaminol dose-dependently inhibited cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…Sesaminol, a phytochemical from sesame oil, has been focused as an antioxidative compound 37, 38, 39 ; however, few studies have reported its anticancer activities. 42, 43 We found that sesaminol could reduce cyclin D1 in a multifaceted manner, such as downregulating the mRNA and protein levels with mTORC1 inhibition and protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Botelho et al, black sesame seed extracts obtained by supercritical CO 2 extraction had neuroprotective effects against a focal brain ischemia model induced by microinjections of peptide endothelin‐1 in the motor cortex of male adult rats. According to Cao et al, sesame seeds are a traditional healthy food in China.…”
Section: Introductionmentioning
confidence: 99%
“…Sesamin is another prominent compound reported in SO that possesses significant protective effects against oxidative stress in animal model including through ameliorate SOD, GPx, reduction of malondialdehyde and elevated different liver marker, TBARS, and lipid peroxidation as well as reduction of superoxide production (Ahmad et al, ; Chen, Ying, Chen, Zhang, & Zhang, ; Hou, Chang, & Jeng, ; Hsieh et al, ; Jeng & Hou, ; Jnaneshwari et al, ; Nakai et al, ; Tian & Guo, ; Zhang et al, ). In vitro studies of sesamin especially in neuronal cell line (PC12), it showed reduction of reactive oxygen species (ROS) generation especially NO production (Cao et al, ; Duarte, Chenet, de Almeida, Andrade, & de Oliveira, ; Lee et al, ; Yashaswini, Rao, & Singh, ). However, Hou et al () reported that 10‐μM sesamin derivative, 3‐bis (3‐methoxybenzyl) butane‐1, 4‐diol, inhibits lactate dehydrogenase, lipid peroxidation, and apoptosis as well as increases ACh release and also prevents cell damage, scavenges ROS, and attenuates the elevation of intracellular free Ca 2+ ion on Aβ‐stressed PC12 cells (Hou et al, ).…”
Section: Resultsmentioning
confidence: 99%